CONDITION OF MANGROVE FORESTS IN DOMPAK URBAN VILLAGE BUKIT BESTARI SUB-DISTRICT RIAU ISLAND PROVINCE - Imanuel, Andrean Nggara; ef, Efriyeldi; Nasution, Syafruddin (Asian Journal of Aquatic Sciences, 2020)
This study was conducted in December 2019, which was located in Dompak Village, Bukit Bestari District, Tanjungpinang City, Riau Islands Province. The purpose of this study was to determine the species composition and condition of mangrove forests based on the value of density, canopy cover and the importance value index of mangroves. The survey method was used in this study, where the data collected was primary data. There are 10 types of mangroves including Avicennia lanata, Bruguiera gymnorrhiza, B. cylindrica, Rhizophora apiculata, R. stylosa, Nypa fruticans, Sonneratia alba, Xylocarpus granatum, Scyphiphora hydrophyllacea and Hibiscus tiliaceus. Mangrove density was in good condition with moderate to dense ​​ranging from 1344.44-1555.56 ind/ha. Canopy cover was in good condition ​​ranging from 61.49-68.47%. The highest importance value index was R. apiculata with a value of 140.32% and the lowest was B. cylindrica with a value of 4.29%.